The Effectiveness of Using Artificial Intelligence ChatGPT (Generative Pre-Trained Transformer) In Qur’an and Hadith Learning Among PAI Students at UIN Sunan Kudus - Zuhaida Hanifah; Supaat Supaat; Abdul Mutholib (Universitas Islam Sultan Agung, 2026)
This study explores the patterns, benefits, challenges, and effectiveness of ChatGPT utilization in Qur’an and Hadith (Qurdis) courses among pre-service Islamic Religious Education (PAI) students at UIN Sunan Kudus, Indonesia. It aims to understand how students employ generative AI as a pedagogical aid while negotiating technological efficiency with the epistemological commitments and scholarly traditions of classical Islamic education in an institution that integrates pesantren values with modern academia. This qualitative case study involved six fourth-semester PAI students (Class of 2024) selected through purposive sampling based on their active enrollment in Qurdis courses, prior experience using ChatGPT, and willingness to participate. Data were collected via in-depth semi-structured interviews, participatory and non-participatory observations, and document analysis including ChatGPT conversation histories, student assignments, and lecture materials. Data analysis followed Miles and Huberman’s interactive model with iterative data reduction, display, and conclusion drawing. Trustworthiness was established through source, methodological, and time triangulation, supplemented by member checking. Findings reveal that students predominantly use ChatGPT for preparatory tasks (drafting lesson plans/RPP, modules, and outlines) and as a supplementary tool for independent learning and group discussions. The tool effectively supports concept simplification, translation, and discussion prompt generation. However, it shows notable limitations in sanad-matan analysis, Hadith grading, and depth of scholarly opinions. Students function as active editors who rigorously verify AI outputs against classical sources and lecturer guidance. Overall, ChatGPT moderately to highly enhances learning efficiency and participation when used critically under supervision, yet it cannot replace the scholarly authority and spiritual dimension (barakah) of traditional Islamic pedagogy.